Techno-economic and financial index analysis for the improvement of entrepreneurship and competitiveness strategies of Greek goat enterprises - Maria, Tsiouni; Dimitrios, Gourdouvelis; Christos, Konstantinidis; Stamatis, Aggelopoulos (Frontiers in Sustainable Food Systems, 2022)
Greece is a country with a long tradition in animal breeding, particularly involving small ruminants and goat farming is an important livestock industry. Despite the high productivity and high quality of products, the goat industry shows low competitiveness due to high production costs compared to other EU countries. For economic sustainability, farms have to be profitable; therefore, it is important to maximize income whilst controlling costs. The aim of this paper is to identify the strengths and weaknesses of the goat breeding industry so that it is not only viable but also competitive. The economic performance of goat farms is evaluated in this study, as well as the factors that influence financial results. Capital formation and production costs composition of the holdings are examined. Moreover, the purpose of the analysis is to draw conclusions regarding the gross return achieved, the participation of production factors (land, labour, capital) in the composition of total costs and the financial results achieved.